The Use of Edmodo in ESP Classroom: A Study on Students’ Perception and Classroom Activities - Mariana Ulfah Hoesny; Hilda Cahyani; Imam Nur Aziz (Universitas Pendidikan Mandalika, 2020)
This study was aimed at investigating the use of Edmodo, an online learning platform in a Garuda Maintenance Facility class in Electronic Engineering study program of State Polytechnic of Malang. In addition, students’ perception toward the use of Edmodo was also explored to find out the advantages and disadvantages of the implementation of Edmodo. This study also investigated teacher’s activities that have been done via Edmodo. The activities done by students via Edmodo are presented in the result of this study to inspire other teachers about how to use Edmodo effectively. This study was a case study since it described and analyzed a group in a classroom setting to gain understanding through activities done in the classroom. Survey and interviews were used to collect the data about students’ perception and the description of classroom activities. The results showed that students had positive perceptions towards the use of Edmodo since it accomodated their need to apply technology in their learning. In addition, it could also encourage shy students who tended to be discouraged when interacted and participated without the aid of online tool in the classroom. Students also mentioned some obstacles encountered during the use of Edmodo such as slow internet connection and limited data package that was needed to connect to the internet. However, it can be concluded that the implementation of Edmodo in GMF class gained positive response. In addition, students also appreciated various activities conducted via Edmodo. It can be added that Edmodo as a learning platform is not only used to replace lecturer’s absence, but it can accomodate various learning activities that can increase communication skills in English.